MMT: Modern Monetary Theory or Magical Monetary Thinking? The empirical evidence - Emilio Ocampo (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2020)
This article presents a summary of the main theoretical arguments and policy recommendations of Modern Monetary Theory (MMT) and traces back its intellectual origins to the writings on money of Georg F. Knapp and on fiscal policy of Abba P. Lerner. It also presents evidence on two countries that followed MMT like policies: Germany between 1939 and 1945 and Argentina with brief interruptions since 1946. The main conclusion of the article is that any country that consistently follows the policy prescriptions of MMT will inevitably experience high inflation and lower (and even negative) economic growth.
Keywords: B00; N14; N16; P40; P47; 330; Monetary Theory; MMT; Argentina